2010
DOI: 10.1007/s10714-010-0935-2
|View full text |Cite
|
Sign up to set email alerts
|

Algebraic analysis of a model of two-dimensional gravity

Abstract: An algebraic analysis of the Hamiltonian formulation of the model two-dimensional gravity is performed. The crucial fact is an exact coincidence of the Poisson brackets algebra of the secondary constraints of this Hamiltonian formulation with the SO(2,1)-algebra. The eigenvectors of the canonical Hamiltonian H c are obtained and explicitly written in closed form.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Hence, the breakdown in space-time is a non-perturbative property of GR (for d ≥ 2) itself. In the following section, we present a summary of results derived in [9][10][11][12][13], whereby, based on these findings we propose that the loss of manifest covariance using the constraint quantization approach is due to its application on the full action. To support our claims, we present a counterexample regarding the successful quantization of non-Abelian gauge Yang Mills theories, where covariance is recovered in the path integral [13].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Hence, the breakdown in space-time is a non-perturbative property of GR (for d ≥ 2) itself. In the following section, we present a summary of results derived in [9][10][11][12][13], whereby, based on these findings we propose that the loss of manifest covariance using the constraint quantization approach is due to its application on the full action. To support our claims, we present a counterexample regarding the successful quantization of non-Abelian gauge Yang Mills theories, where covariance is recovered in the path integral [13].…”
Section: Introductionmentioning
confidence: 94%
“…where B αβγµνρ = g αβ g γρ g µν − g αµ g βν g γρ + 2g αρ g βν g γµ − 2g αβ g γµ g νρ . For this action, it was found that the constraints are first class [11] for d > 2 dimensions, and similarly for d = 2 dimensions [12] for which the following path integral by Fadeev [17] applies:…”
Section: Canonical Quantization Of D ≥ 2 Dimensional Gr Via Canonical...mentioning
confidence: 99%